Amelioration Effects of Soil Fertility and Microbial Responses on a Sandy Loam Soil in Mining Areas Treated with Biochar and Water Jet-Loom Sludge - Mengmeng Jiang; Xiaofang Zhu; Xunzheng Rao; Jiu Huang (Land)
Aiming at the remediation of soil in mining areas caused by mining activities, pot experiments were conducted using water jet-loom sludge (WJLS) and biochar as soil amendments to evaluate their potential for enhancing soil fertility and microbial communities of degraded mining soils. Six treatments with varying WJLS (0%, 5%, 15%) and biochar (0%, 3%) application rates were evaluated. Results showed that WJLS can significantly improve soil organic carbon (OC), total nitrogen (TN), total phosphorus (TP), and microbial biomass, while reducing soil pH and enhancing ryegrass biomass by 1.6–4.1 times. However, a 3% biochar addition may increase the soil sodium absorption ratio (SAR). Moreover, the role of biochar was mainly reflected in the microbiological properties. The combining of WJLS and biochar increased the soil microbial biomass and obviously improved the diversity and abundance of bacteria and fungi in the soil (p < 0.05) after the amendment, especially in the biochar addition groups. At the phylum level, the relative abundance of Proteobacteria, Firmicutes, and Actinobacteriota accounted for 72.4%~84.2% of soil bacteria in all treatments, while the fungi were dominated by Ascomycota (58.30%~95.36%) and Fungi_unclassified (1.26%~38.97%), all of which were significantly related to enhanced soil properties especially OC, TN, TP, and cation exchange capacity (CEC). Overall, WJLS and biochar demonstrate strong potential as sustainable amendments for improving soil fertility and biological quality in the reclamation of mining-affected lands.